Selective glycogen depletion pattern in human muscle fibres after exercise of varying intensity and at varying pedalling rates - Gollnick, P. D.; Piehl, K.; Saltin, B. (The Journal of Physiology, 1974)
1. Glycogen depletion pattern in human skeletal muscle fibres was studied after bicycle exercise of varying intensity performed at different pedalling rates. Work intensities studied were equivalent to 30-150% of VO2 max. with pedalling rates of 30-120 rev/min.